Gestión de riesgos ambientales para oleoductos en Colombia (2017)
In this monograph, the environmental risk was analyzed and evaluated in a section of the Caño Limón-Coveñas pipeline, between the first PS-1 pumping station and the community of San José de la Pesquera. Information was gathered on the immediate environment, the economic aspects of the project, the environmental and institutional aspects to advance in the identification of possible events with high potential to materialize, the causes and consequences related to possible events or incidents, to the existing risks in the pumping station, the section of the pipeline and the community.